1998
DOI: 10.1590/s1020-49891998001200006
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium oocysts and Giardia cysts in water supplies of San Pedro Sula, Honduras

Abstract: During June 1996, water supplies of the city of San Pedro Sula, Honduras, were sampled to obtain an assessment of Cryptosporidium oocyst and Giardia cyst concentrations. Each sample was concentrated and stained with an indirect immunofluorescent antibody, and parasites were counted through microscopic analysis. In three surface water supplies, Cryptosporidium oocyst concentrations ranged from 58 to 260 oocysts per 100 L, and Giardia cysts were present in concentrations ranging from 380 to 2100 cysts per 100 L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The concentration of human pathogens from ambient water by C. ariakensis triploids and retention of these pathogens without (or with minimal) inactivation and a very low depuration rate provide evidence that these oysters will present a public health threat to the human food chain if they are harvested from polluted water. This conclusion is reinforced by the concentration of waterborne pathogens (25 cells/liter/day) used in the present study, which was representative of pathogen levels observed in surface waters, including the Chesapeake Bay (9,21,33,34,37). The concentrations of waterborne C. parvum oocysts measured in the Nanticoke, Patuxent, and Potomac Rivers and the Tangier Sound were 79, 31, 10, and 8 oocysts/ liter, respectively (9).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The concentration of human pathogens from ambient water by C. ariakensis triploids and retention of these pathogens without (or with minimal) inactivation and a very low depuration rate provide evidence that these oysters will present a public health threat to the human food chain if they are harvested from polluted water. This conclusion is reinforced by the concentration of waterborne pathogens (25 cells/liter/day) used in the present study, which was representative of pathogen levels observed in surface waters, including the Chesapeake Bay (9,21,33,34,37). The concentrations of waterborne C. parvum oocysts measured in the Nanticoke, Patuxent, and Potomac Rivers and the Tangier Sound were 79, 31, 10, and 8 oocysts/ liter, respectively (9).…”
Section: Discussionsupporting
confidence: 69%
“…The inoculum of C. parvum oocysts, G. lamblia cysts, and spores of human-infectious microsporidia simulated the concentration of these pathogens reported for surface waters, including the Chesapeake Bay (9,33,34,37).…”
mentioning
confidence: 99%
“…These protozoans can be detected in several water sources including wastewaters, surface waters, spring waters, recreational waters, ground waters and drinking waters (Solo-Gabriele et al 1998;Franco et al 2001;Rose et al 2002;Hachich et al 2004;Briancesco & Bonadonna 2005;Ryu & Abbaszadegan 2008;Muchiri et al 2009). …”
mentioning
confidence: 99%
“…Concentration of oocysts and cysts in the Delaware River, New Jersey, USA (drawn by drinking water plants) was 14 and 40 per 5 l, respectively (Atherholt et al 1998), and 260 and 2,100 per 100 l, respectively, in water supplies of San Pedro Sula, Honduras (Solo-Gabriele et al 1998). The present study demonstrated that zebra mussels and Corbicula clams performed very well as indicators for waterborne contamination under the pollution levels reported from surface drinking water supplies (Rose et al 1997;Atherholt et al 1998;Solo-Gabriele et al 1998). This conclusion is reinforced by the negative results of water testing by the method recommended by the U.S. Environmental Protection Agency (Rodgers et al 1999a, b).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, studies on wild-collected oysters that utilized immunofluorescent antibody against both Cryptosporidium and Giardia never identified Giardia, whereas the load of Cryptosporidium was quite high (Fayer et al , 1999. Cryptosporidium and Giardia originate from similar sources and Giardia usually occurs in higher concentrations than Cryptosporidium in surface water (Atherholt et al 1998;Solo-Gabriele et al 1998). This may indicate that Giardia cysts do not resist digestion and disintegrate in the tissue of molluscan shellfish.…”
Section: Discussionmentioning
confidence: 99%